2012
DOI: 10.1209/0295-5075/97/28010
|View full text |Cite
|
Sign up to set email alerts
|

The electric double layer at high surface potentials: The influence of excess ion polarizability

Abstract: By including excess ion polarizability into Poisson-Boltzmann theory, we show that the decrease in differential capacitance with voltage, observed for metal electrodes above a threshold potential, can be understood in terms of thickening of the double layer due to ion-induced polarizability-holes in water. We identify a new length which controls the role of excess ion polarizability in the double layer, and show that when this is comparable to the size of the effective Debye layer, ion polarizability can signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
122
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 43 publications
5
122
0
Order By: Relevance
“…The solvation shell around an ion lowers the local permittivity and leads to an additional dielectrophoretic force in a field gradient. These "excess ion polarizability" phenomena were perhaps first noted by Bikerman [14] and recently included by Hatlo, van Roij and Lue in an MPB model, which improves predictions of double-layer capacitance [17]. Bonthuis and Netz have also shown that continuous variations in dielectric permittivity near a surface can improve the description of electrokinetic phenomena [18,19].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The solvation shell around an ion lowers the local permittivity and leads to an additional dielectrophoretic force in a field gradient. These "excess ion polarizability" phenomena were perhaps first noted by Bikerman [14] and recently included by Hatlo, van Roij and Lue in an MPB model, which improves predictions of double-layer capacitance [17]. Bonthuis and Netz have also shown that continuous variations in dielectric permittivity near a surface can improve the description of electrokinetic phenomena [18,19].…”
mentioning
confidence: 74%
“…The classical effect of dielectric saturation reduces the permittivity at large fields due to the alignment of solvent dipoles [32,[37][38][39], although an increase in dipole density near a surface may have the opposite effect [40]. A recent model which included excess ion polarizability demonstrated excellent agreement with experimental capacitance data on surfaces with no adsorption [17].…”
Section: B Modifications For Chemical Effectsmentioning
confidence: 97%
“…Approximations enter the theory at the level of (∂Ψ/∂T ) Q , so that more accurate estimates can be found by systematically improving the grand potential Eq. (3), by including, for instance, solvent polarizability [38], a better description of excluded volume interactions [39], and residual ion correlations [29] (see also Appendix C).Though oversimplified ideal-gas reasoning permeates 5 the reversible heating literature [9,11,[13][14][15], the main finding of this Letter is that the thermodynamic identity Eq. (2), and not Eq.…”
mentioning
confidence: 91%
“…The mean-field nature of the PB equation does not allow us to take into account the effects of the ionic correlations, whereas the consideration of the solvent as a continuous dielectric medium makes it impossible to study the effects of the solvent molecular structure. These two factors motivated the researchers to find new approaches the PB equation modifications during the last two decades [1][2][3].Nowadays, great efforts have been made to modify the PB equation with respect to ionic correlations [4][5][6][7][8], the dipole structure of the solvent [9][10][11]16], polarizability and permanent dipole of ions [13][14][15][16] as well as their excluded volume [17][18][19][20][21], and finally solvent quadrupolarizability [22]. These modifications sufficiently improved the theory of electrolytes that enabled calculations of the physico-…”
mentioning
confidence: 99%
“…Nowadays, great efforts have been made to modify the PB equation with respect to ionic correlations [4][5][6][7][8], the dipole structure of the solvent [9][10][11]16], polarizability and permanent dipole of ions [13][14][15][16] as well as their excluded volume [17][18][19][20][21], and finally solvent quadrupolarizability [22]. These modifications sufficiently improved the theory of electrolytes that enabled calculations of the physico-(a) E-mail: urabudkov@rambler.ru (b) E-mail: bancocker@mail.ru chemical characteristics of real solutions, such as dielectric permittivity and activity coefficients [11,22].…”
mentioning
confidence: 99%